Relationship between sudden natural death and abdominal fat evaluated on postmortem CT scans. (20th January 2017) - Kaichi, Y.; Sakane, H.; Higashibori, H.; Honda, Y.; Tatsugami, F.; Baba, Y.; Iida, M.; Awai, K.
Summary: Objective: This study examined the association between sudden natural death and abdominal fat using postmortem computed tomography (CT) scans. Subjects and methods: Postmortem CT images at the umbilical level of 241 subjects were used to measure abdominal areas of subcutaneous‐ and visceral fat, the rate of visceral fat and the waist circumference. Of the study subjects, 174 died of sudden natural death (130 men and 44 women), and 67 died of different causes (46 men and 21 women). All were between 40 and 75 years of age. Logistic regression analysis was performed to identify independent abdominal parameters associated with sudden natural death. Results: By univariate analysis, the areas of subcutaneous and visceral fat were significantly larger in sudden natural death than who died of different causes (subcutaneous fat, odds ratio [OR] = 1.004, 95% confidence interval [CI] = 1.000–1.007, p  = 0.03; visceral fat, OR = 1.008, 95% CI = 1.003–1.013, p  < 0.01). Multivariate analysis showed that the area of visceral fat was an independent factor associated with the risk of sudden natural death (OR = 1.008, 95% CI = 1.002–1.015, p  = 0.02). Conclusions: Postmortem CT revealed that sudden natural death was related to abdominal fat deposits.